Tillage practices and nitrogen rates influenced wheat and sorghum yield and nitrogen use efficiency in long-term dryland wheat-sorghum rotation system - Majrashi, Mosaed Abdullah (Kansas State University, 2020)
A major challenge for agronomists is developing cropping systems that exhibit superior performance across variable environmental conditions. Long-term field research trials provide a direct measure of the effect of environmental conditions within the context of treatment effects. Winter wheat (Triticum aestivum L.) is the most widely grown base crop in dryland systems of the semiarid central Great Plains, but grain yields are limited by nitrogen (N) and soil water availability. The goal of this research was to assess long-term cropping systems of winter wheat-grain sorghum-fallow in dryland. The focus was to determine the effect of three tillage practices and rates of N fertilization rates effects on the efficiency of the management system and grain yields for 2015-2018, and evaluate the yield stability for both crops in a 53-year-old crop rotation and fertility experiment. In the first study we evaluated the long-term effects of three different tillage practices and four N fertilizer rates on grain yield, protein content, and N use efficiency indices of winter wheat and grain sorghum in 2015-2018. The experiment was conducted on a long-term plot initiated in 1965 in Hays, KS as a split-split-plot arrangement of rotation, tillage, and N fertilizer treatments with four replications in a randomized complete block design. The main plots were the crop phase (winter wheat, grain sorghum, or fallow), sub-plots were three tillage treatments [conventional tillage (CT), reduced tillage (RT), and no-tillage (NT)]. The sub-sub-plots were four N rates (0, 22, 45, and 67 kg N ha⁻¹) later modified in the 2015 growing season to 0, 45, 90, and 134 kg ha⁻¹. Results showed tillage × N rate interaction had no significant (P = 0.608) effect on grain yield. Year × tillage and year × N rate had significant (P < 0.0001) effect on grain yield. Across N rates, grain yield, NAE and ANR were more in soils under NT compared with CT or RT. Grain yield under NT increased by 8 kg ha⁻¹ for every mm of growing season precipitation compared with 4 kg ha⁻¹ with CT or RT. Nitrogen application significantly (P < 0.05) increased grain yield and protein concentration, but NAE and ANR decreased beyond 45 kg N ha⁻¹. Our results showed NT is the best management practice to increased grain sorghum yields, N use indices and sustainability in dryland systems. Winter wheat yield with CT was greater than RT or NT, but tillage had no significant effect on ANR, NAE or N utilization efficiency (NUtE, kg grain/ kg total N uptake) averaged across the four-years. Grain yield, protein content, total N uptake, and NUtE of winter wheat increased with increasing N rates. But the NAE and RAN decreased at higher N rates. Tillage systems had little effect on the total N uptake and NUE indices. The benefits of NT can be realized with appropriate N fertilization. However, the extent of that benefit and the appropriate N fertilization rate depends on the amount and timing of precipitation during the growing season. That benefit also depends on the effectiveness of weed control practices. A second study was conducted to evaluate the long-term effects of three different tillage practices in four N fertilizer rates on yield of winter wheat and grain sorghum, yield trend, and yield stability from 1975 to 2014. We hypothesized that yield would be higher, more stable, and increase more over time in i) NT practices compared to most intensive tillage CT and RT systems, and ii) highest N fertilizer rate compared to unfertilized control and 20 kg N ha⁻¹. The stability analysis showed grain yield with each tillage practice was more stable with increasing N fertilizer rates. The data created from this long-term experimental study of winter wheat-grain sorghum- fallow production systems showed temporal variability in yield for both crops, which was evident with all treatment combinations. An analysis of variances was shown that practices were a significant factor for predicting yield in 24 out of 31 years (77% of years) for winter wheat in 17 out 30 years (57% of years) for grain sorghum. N fertilizer rate was a significant factor for predicting yield in 31 out of 31 years (100% of years) for winter wheat in 27 out 30 years (90% of years) for grain sorghum during the study periods at significant level of 0.05. Yield stability analysis indicated yields under NT responded poorly in winter wheat or equally in grain sorghum in low-yielding environments compared to the more intensive tillage practices of CT or RT. In high-yielding environments CT and RT produced greater yields than NT. In general, N fertilizer application resulted in more stable yields compared to unfertilized controls. This effect was more pronounced in low yielding environments for both crops. When fertilized, NT production in low yielding environments generated yields comparable to CT or RT treatments. The amount and distribution of precipitation throughout the growing season or during the fallow period preceding crop planting were the most important factors influencing yields of both crops, though that impact was influenced by N fertilization rate. Overall, yield stability analysis indicated that the use of RT or CT along with adequate N fertilization produced higher wheat yields across all yield environments compared to NT.
Keywords: Winter Wheat; grain sorghum; Yield and Yield Stability; nitrogen use efficiency; conventional tillage; no tillage